Educational Supervision to Develop Pedagogical Competence of Kindergarten Teachers - Agoes Dariyo; Tarish Daffa Rabbani; Ezra Andrianputra (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2026)
The main problem faced by kindergartens in the hamlet of Tegalbedug, Lelea, Indramayu, West Java, is the low competence of teachers as professional educators, because their highest level of education is high school or equivalent. They cannot yet be called professional teachers, but due to the limited number of teachers in the area, school leaders are forced to recruit teachers who do not meet the minimum education standards. The negative impact of this is the low quality of teaching in kindergartens. To overcome this problem, the Head of Tegal Bedug Hamlet requested the assistance of lecturers as professionals. This educational supervision activity was intended to equip teachers with the basic knowledge required of professional teachers, thereby improving their pedagogical competence. The method used was lectures, question and answer sessions, and discussions. The participants were kindergarten teachers. This activity was carried out using a one group pretest and post-test approach. Data collection was conducted using a questionnaire on pedagogical competence given to teachers before the activity (pretest) and after the activity (post-test). Data analysis was performed using a t-test. The analysis results showed a difference between the pre-test and post-test results, namely pre-test score (36.8) < post-test score (38.4), meaning that educational supervision can significantly improve teachers' pedagogical competence.